FFR guided PCI on long coronary lesions: 2-year clinical results with 2nd or newer generation DES - Baranauskas, Arvydas; Bajoras, Vilhelmas; Budrys, Povilas; Laucevičius, Aleksandras; Davidavičius, Giedrius (Acta medica Lituanica, 2016)
Background. Despite improvements in drug-eluting stent (DES) technology, treatment strategies for long coronary artery lesions remain a controversial issue. The aim of our study was to evaluate the long-term clinical results after FFR guided PCI on long coronary lesions. Materials and methods. A total of 74 consecutive patients with significant (mean FFR 0.61 ± 0.11) coronary artery lesions ≥30 mm in length were included in the prospective study. All patients were treated with FFR guided PCI implanting newer generation Biolimus, Everolimus or Zotarolimus eluting stents. Clinical endpoints – target vessel revascularization (TVR) and major adverse cardiac events (MACE) – were recorded at 1 and 2 years. Results. 100% angiographic procedure success was achieved, the mean post procedural FFR was 0.88 ± 0.06. At 2-year follow-up, 6 (8.1%) patients had ischemia driven TVR, all within the first 12 months. There were no target vessel related acute coronary syndromes and definite stent thromboses in the study group. At 2 years, the total MACE rate was 29.7%. There was a trend towards a higher TVR rate in patients with overlapping DES vs single DES implanted (9.6 vs 4.5%, p = 0.6). On regression analysis, the total stent length had no influence on the TVR rate. Conclusions. At 2 years after stenting long coronary lesions with newer generation DES the TVR rate was 8.1%, which is acceptable in the high cardiovascular risk population with diffuse coronary artery disease. The total stent length did not affect the long-term clinical outcomes.